Modeling, simulation and operation of a simulated moving bed for continuous chromatographic separation of 1,1'-bi-2-naphthol enantiomers - Pais, Luís S. (1997)
The objective of this paper is to study the separation of enantiomers of 1,1′-bi-2-naphthol in 3,5-dinitrobenzoyl phenylglycine bonded to silica gel, using heptane–isopropanol (72:28) as eluent by simulated moving bed chromatography (SMB). A model for the prediction of the cyclic steady state performance of the SMB, based on the analogy with the true moving bed, is developed assuming axial dispersion flow, linear driving force approximation for intraparticle mass transfer and multicomponent adsorption equilibria. The SMB package allows the simulation of the pilot unit. The effect of several operating parameters on the SMB performance is analyzed. The performance is characterized by purity, recovery, solvent consumption and adsorbent productivity. The package is an important tool for learning and training operators, allowing the choice of best operating conditions. The operation of the SMB pilot unit was carried out for the separation of racemic mixtures using a 8-column configuration. Purities and recoveries higher than 95% in the extract and raffinate were obtained. Model and experimental results are compared and the package is also used to predict the steady state internal profiles for the SMB operation in good agreement with experimental results.